STUDI PERBAIKAN CARA PENYADAPAN KOPAL DI KPH SUKABUMI - Soenarno Soenarno; Maman Mansyur Idris; Zakaria Basari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
Copal from Agathis tree has been one of important forest products, not only as export commodity but also as raw material for some induatries. In the last few years however production in this country began to decrease, due to inefficient tapping by the forest worker.Because of this reason a study on the tapping procedure is necessary. Thia report deals with a preliminary study on the present “quarre” type of tapping procedure commonly adopted by the forest worker. The locality chosen was Gede Barat Sub forest district at Sukabumi, West Java.Three factors were chosen for the tapping study, namely the effect on of resin productivity of the location of the wound with respect to west and east direction (factor A), time of tapping (factor B) and type of wound covering (factor C). The result of this study show that :Covering of tap wound does not cause incoveniences to the worker.Resin productivity is not significantly affected by the wound location.The highest production of the resin per tree comes from the wound cut in the morning and covered with black coloured polyethelene sheet.